1994
DOI: 10.1177/001872089403600412
|View full text |Cite
|
Sign up to set email alerts
|

Young Children's Ability to Climb Fences

Abstract: Three studies were performed to evaluate the fence-climbing abilities of children who are in the high-risk age group for drowning in residential pools. Study 1 examined the ability of children in the age range of 24 to 54 months to climb commonly used fences (common chain link, small chain link, picket, iron, and stockade) at a 4-ft (1.22-m) height. Study 2 examined children's abilities to climb fences retrofitted with features that would potentially make them more difficult to climb. Study 3 examined children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 1 publication
1
10
0
Order By: Relevance
“…This has resulted in wide variation in fencing regulations across jurisdictions, with only some requiring fencing for portable pools. 17 In addition, portable pools often fall outside of local building codes that require pool barriers. 7,8 Children in the present study primarily entered the pool using the pool ladder (ϳ68%) or by climbing on a nearby object (ϳ20%).…”
Section: Wading Pool Submersionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This has resulted in wide variation in fencing regulations across jurisdictions, with only some requiring fencing for portable pools. 17 In addition, portable pools often fall outside of local building codes that require pool barriers. 7,8 Children in the present study primarily entered the pool using the pool ladder (ϳ68%) or by climbing on a nearby object (ϳ20%).…”
Section: Wading Pool Submersionsmentioning
confidence: 99%
“…An estimated 3000 children in this age group were treated annually in US hospital emergency departments for injuries associated with pool submersion from 2006 through 2008. 14 Private pools have been found to be the most frequent site of submersion injury for US children, 2,5,6,9,[11][12][13][14][15][16][17] and 54% of fatalities associated with pools reported to the US Consumer Product Safety Commission (CPSC) for children younger than 5 years during the period 2005 through 2007 occurred at the child's home. 18 Despite these statistics, many pool owners do not perceive their pool as a hazard for young children.…”
mentioning
confidence: 99%
“…In 1 study, chain-link fences were easily scaled by children, whereas ornamental ironbar fences proved more difficult to climb. 61 Fences should be at least 4 ft high, and no opening under the fence should be more than 4 in (some building codes require a 5-ft fence and a maximum fence-to-ground distance of only 2 in). Vertical members of the fence should be less than 4 in apart to keep a child from squeezing through them, and there should be no footholds or handholds that could help a young child climb the fence.…”
Section: Pool Fencingmentioning
confidence: 99%
“…These conditions might have resulted in the lack of any fencing around some pools or the use of ineffective barriers. For example, Rabinovich et al 49 showed that children as young as 24 months can successfully climb over common 5-foot chain-link fences. Furthermore, inadequate fencing might give parents a false sense of security, which could reduce their level of supervision of young children.…”
Section: Discussionmentioning
confidence: 99%